Stereotactic body radiotherapy for medically unfit patients with cancers to the head and neck. Issue 8 (21st March 2020) - Al‐Assaf, Hossam; Erler, Darby; Karam, Irene; Lee, Justin W.; Higgins, Kevin; Enepekides, Danny; Zhang, Liying; Eskander, Antoine; Poon, Ian
Abstract: Background: A single institutional experience of stereotactic body radiation therapy (SBRT) to medically unfit patients with unresectable head and neck cancers (HNCs). Methods: A retrospective review of HNC patients undergoing SBRT was undertaken from 2011 to 2016 for fractionation ranges between 35 and 50 Gy in 4 to 6 fractions. Results: One hundred and fourteen patients with 117 SBRT courses were included with mean follow‐up of 10.5 months. The cohort consisted of previously untreated primary HNC (n = 48), recurrent never irradiated HNC (n = 19), oligometastatic (n = 17) non‐HNC primaries and previously irradiated HNC (n = 33). Local control (LC) at 12 months and median progression free survival was 85.8%, 78.2%, 85%, 78.9% ( P = .86) and 23.7, 14.8, 10.5 and 7.8 months ( P = .04) respectively. Only one patient had an acute grade 4 toxicity, two patients had grade 4 late toxicities. Conclusions: HNC SBRT is an effective treatment for frail patients where longer LC is relevant but are unable to tolerate protracted radiation schedules.